Using alternative buffer for DNA genomic isolation in forest trees - Mahadi, Imam; Zulfarina,; Anggraini, Megawati (Jurnal Penelitian Kehutanan Wallacea, 2021)
DNA optimization procedures can be carried out on the type of buffer used during extraction or physical handling techniques in separating genomic DNA from other compounds. The research using Three types of buffer: 1. CTAB, 2. Detergents containing Alkyl Benzene Sulfonate (ABS) surfactants and Three Detergents containing Sodium Laureth Sulphate (SLS) surfactants. This study aims to obtain an optimal DNA isolation method to produce genomic DNA of good quality and sufficient quantity so that it can be used for genetic diversity analysis in forest trees and to determine the optimal alternative buffer for CTAB to facilitate DNA isolation in remote areas, which generally hard to get CTAB. The parameters measured in this study were the presence of DNA and DNA concentration. The results showed that DNA isolation of 12 species of forest trees was successfully carried out using CTAB buffer and Detergent containing ABS surfactants by visualizing the genomic DNA bands from the results of the electrophoresis and Nanodrop spectrophotometer meanwhile Detergent containing SLS surfactants buffer was not successful in DNA isolation. The highest DNA quantity (DNA concentration) was found in 19 samples using CTAB buffer and the detergent containing ABS surfactants buffer with a concentration of 1403,8 - 3412,7 ng/μl. The conclusion of this study was CTAB buffer and the Detergent containing ABS surfactants can also be used as an alternative to a simple buffer for DNA isolation experiments.